Potential health risk and bio-accessibility of metal and minerals in saltpetre (a food additive). Issue 3 (March 2023) - Nkansah, Marian Asantewah; Korankye, Mavis; Darko, Godfred; Dodd, Matt; Opoku, Francis
Abstract: Food additives are used to enhance freshness, safety, appearance, flavour, and texture of food. Depending on the absorbed dose, exposure method, and length of exposure, heavy metals in diet may have a negative impact on human health. The X-Ray Fluorescence (XRF) Analyzer from Niton Thermo Scientific (Mobile Test S, NDTr-XL3t-86956, com 24) was used in this work to measure the heavy metal content in saltpetre, a food additive that mostly contains potassium nitrate. The average essential metal concentrations in the samples were determined to be 27044.27 ± 10905.18 mg kg −1, 24521.10 ± 6564.28 mg kg −1, 2418.33 ± 461.50 mg kg −1, and 4.615 ± 3.59 mg kg −1 for Ca, K, Fe and Zn respectively. Toxic metals (As, Pb) were present in the saltpetre samples at 4.13 ± 2.47 mg kg −1 and 2.11 ± 1.87 mg kg −1 average concentrations. No traces of mercury or cadmium were detected. Studies on exposure, health risks, and bio-accessibility identified arsenic as a significant risk factor for potential illnesses. The need to monitor heavy metal content of saltpetre and any potential health effects on consumers is brought to light by this study.